The role of stakeholders in relation to the business model in the taxi industry - Bitsch, Jakob; Brochstedt, Sara; Holm, Alexander Hjerrild; Knudsen, Andreas (Proceedings of Pragmatic Constructivism, 2017)
This paper illustrates how business models and business model innovation are related to the theory of stakeholders. The paper explores how lack of business model innovation in the taxi industry, can be explained by the relation to the power and interests of its stakeholders. The authors have employed an explanatory case study, using multiple sources of evidence, primarily archival records and observations. The research reveals that the business model of the taxi industry have not experienced major changes, even though the environment surrounding the taxi industry have seen several changes. An analysis of the stakeholders of the taxi industry explains that the lack of business model innovation is a consequence of the misfit between the power of the taxi industry and government, and the customers. The paper contributes to the existing literature of business models, business model innovation and stakeholder theory, and their relation in between.